How Much Is Too Much? The Impact of Update Frequency on Crowdfunding Success - Eliran Solodoha (Administrative Sciences)
This research seeks to clarify the uncertainty in crowdfunding literature regarding the relationship between the number of updates and campaign success. By integrating signal theory and the notion of information overload, this study posits a curved, inverted U-shaped relationship between the number of updates and campaign success. Empirical evidence to support this hypothesis is drawn from an analysis of 2852 projects sourced from a reward-based crowdfunding platform. The aim of this inquiry is to provide insights into the intricate dynamics that influence how the number of updates impacts the results of crowdfunding campaigns.